Instructional resources as determinants of english language performance of secondary school high- achieving students in Ibadan, Oyo State (2015)
This study examined the role played by instructional resources in enhancing performance of students, especially that of high-achievers, in English Language. The study is descriptive in nature and it adopted a survey design. Simple random sampling technique was used for the selection of fifty (50) SSI - SSIII students from five schools in Ibadan North Local Government Area of Oyo State. The age range for thè participants was from 13 to 18 years. Data were collected using a self-designed instrument with a reliability coefficient of 0.86. Two research questions were raised and thè research lasted for four weeks. Data collected were analyzed using Pearson Product Moment Correlation. The findings showed that instructional resources play a significant role in enhancing performance of high-achieving students in English Language (r = -.145, N = 50, P > .05). The findings also revealed that there is a significant relationship between thè use of audio, visual and audiovisual materials and performance of high-achieving students in English Language (r =,1067, N = 50, P > .05). Based on these findings, the teachers are encouraged to always make use of instructional resources like audio, visual and audio-visual materials while imparting knowledge and students must as well pay rapt attention in the class whenever instructional resources are being used for them in order to maximize their performance in English Language.